Computational hydraulic simulations for vortex drops - Yeo, Pei Qi (2018)
Underground stormwater drainage and sewer systems are becoming popular globally due to the rising need for land resources optimization with rapid urbanization. The underground systems have been practically applied in densely populated cities such as Hong Kong and Singapore. One of the crucial parts of designing such an underground system is the design of vortex drops, which are commonly used to transport water from higher elevation ground to underground structure safely. These vortex drops induce swirling flow along the dropshafts and dissipate energy by utilizing the turbulence generated and friction on the wall of dropshaft. Although there are many design guidelines and theoretical models available, the individual design of vortex drops needs to be validated. In addition to conventional physical model testing, Computational Fluid Dynamics (CFD) can also be an economical alternative to evaluate the hydraulic performance of vortex drops design. The minimum air core ratio, one of the most important design parameters of vortex drop, is strongly dependent on the dropshaft geometry. Previous studies on air core ratio mainly focused on analytical and experimental models. In this project, two-phase numerical simulations of tangential dropshaft had been performed using the commercial software FLUENT and opensource software OpenFOAM. The results from these simulations were then compared to various works done by other researchers reported in the literature. The comparison suggested that useful information can be obtained from the two software for design validation of vortex dropshaft.